Leading beyond the walls - Goldsmith, Marshall; Hesselbein, Frances; Somerville, Iain.; Peter F. Drucker Foundation for Nonprofit Management (San Francisco : Jossey-Bass, 1999)
"Leading Beyond the Walls brings together thought leaders to describe new ways of building relationships, new approaches to strategy and marketing, new models of employee relations, and other innovative ways of thinking and acting. They share practical insights on the challenge of leading in an age when the old rules and conventional boundaries no longer exist. Their essays herald a world in which new possibilities can come only from leaders and organizations willing to move beyond the walls of inertia and tradition."--BOOK JACKET.
Introduction : the community beyond the walls / Frances Hesselbein -- The new pluralism / Peter F. Drucker -- And the walls came tumbling down / Jim Collins -- Preparing for leadership / C.K. Prahalad -- Leading the distributed organization / William Bridges -- Dissolving boundaries in the era of knowledge and custom work / Sally Helgesen -- Decision making beyond the boundaries / Charles Roussel -- Leadership in living organizations / Peter M. Senge -- Maximizing creative collaboration / Dave Ulrich -- Culture is the key / Regina E. Herzlinger -- The power of choice / Stratford Sherman -- Leadership beyond the walls begins with leadership within / Eli Cohen, Noel Tichy -- The mind-set and skill-set of a leader / Steven R. Covey -- New competencies for tomorrow's global leader / Marshall Goldsmith, Cathy Walt -- How to foster champions / Robert Porter Lynch -- Creating success for others / Jim Belasco -- Leading successful change initiatives / Christopher Cappy, Robert Anthony -- The four cardinal principles of leadership / Arun Gandhi -- Leading in a leaderless world / Iain Somerville, D. Quinn Mills -- Principles of effective collaboration / Patrick J. Waide Jr. -- Creating a future we wish to inhabit / Rita Harmon, Mel Toomey -- Strategies for win-win alliances / Roxanne Spillett -- Building civic coalitions / Richard E. Cavanagh -- New models of public leadership / Joseph S. Nye Jr.
"The Peter F. Drucker Foundation for Nonprofit Management"--P. [iv].
Includes index.
Keywords: Leadership; Management; Organizational change